1999
DOI: 10.1063/1.369229
|View full text |Cite
|
Sign up to set email alerts
|

Role of silicon impurities in the trapping of holes in KTiOPO4 crystals

Abstract: Electron paramagnetic resonance ͑EPR͒ has been used to characterize a new hole trap in flux-grown KTiOPO 4 crystals. This center is formed at room temperature when the crystals are exposed to either 60 kV x rays or a pulsed 355 nm laser beam. Principal g values measured at room temperature are 2.0030, 2.0102, and 2.0320. The intensity of the EPR spectrum is considerably larger in a silicon-doped sample, thus suggesting that the responsible defect consists of a hole trapped on an oxygen ion adjacent to a silico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Stevens et al [72] have identified O − next to a Si 4+ ion on a P 5+ site in the non-linear optic material KTiOPO 4 (KTP) and an accompanying absorption band with M = 2.5 eV [10]. With such a sample, the EPR of the O − defect sketched in figure 22 is observed.…”
Section: Materials With Indications For Further O − Bound Polaron Abs...mentioning
confidence: 99%
“…Stevens et al [72] have identified O − next to a Si 4+ ion on a P 5+ site in the non-linear optic material KTiOPO 4 (KTP) and an accompanying absorption band with M = 2.5 eV [10]. With such a sample, the EPR of the O − defect sketched in figure 22 is observed.…”
Section: Materials With Indications For Further O − Bound Polaron Abs...mentioning
confidence: 99%
“…This centre thermally decays near 160 K. Other centres in KTP have the hole (i.e. unpaired electron) trapped on an oxygen ion adjacent to an aluminium ion [10,17] substituting for a titanium, or a silicon ion [18] substituting for phosphorus. A different type of hole-like centre occurs when a platinum atom (Pt 0 ) substituting for a potassium ion traps a hole and becomes a Pt + ion [19], or when a silver ion (Ag + ) substituting for a potassium ion traps a hole and becomes a Ag 2+ ion [20].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the weak ENDOR lines in Fig. 2 may be due to hyperfine interactions associated with low concentrations of underlying perturbed hole centers, i.e., similar holelike centers that have their EPR signals in the same magnetic field region as our primary hole center [22]. Figure 3(a) shows the 40 K EPR spectrum of the hole center when the magnetic field is parallel to the a-axis of the crystal.…”
Section: Rb Andmentioning
confidence: 97%